An Analysis of Linguistic Choices in Legal Drafting - Mbanugo, Comfort Goma; Ezeifeka, Chinwe (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2024)
This research analyses the register choices and the language of Law. The language of law has been found to be too difficult for a layperson to comprehend. This is so because the wordings are unique and peculiar to the profession. This specialised use of language through the register choices makes interpretation and understanding of laws, legal processes, documents and proceedings a herculean task. This is the crux of this study. It is based on the foregoing that this study seeks to unravel the unique register choices used in legal documents in order to ascertain the extent to which it makes or mars the understanding of these documents and also to find out to what extent the intended purpose is achieved. The paper also examines and analyses the abstruse words used by lawyers in the course of speaking and writing legal documents. The present study adopted a qualitative research design. For the method of data collection, there is direct lifting of sentences and words from the selected documents and texts which are textually analysed. This present study found that the language of law is highly technical. This variety of language use does not enhance the layman’s understanding of legal documents, because the language lacks clarity and brevity. The paper concludes that this unique and professional way of language use bestows on the language of law a peculiarity and distinctiveness that is different from other varieties.